Image Similarity Detection Application Using The Ratcliff/Obershelp Method And Levenshtein Distance - Abdul Halim Hasugian; Suandi Padang (Bahasa Indonesia, 2023)
Searching images with a similarity level of two images in a set of files with the Ratcliff/Obershel and Levenshtein Distance algorithms is expected to help human work. This algorithm is one of the algorithms that can be used to find the similarity of two images by taking the rgb value of each rgb of the pixels of each image. The search process to get the image with the highest similarity. The image format that can be input into the system is a bitmap image. Bitmap mapping of computer graphic images consisting of points that form rows and columns, images consisting of dots and pixels. In the bitmap format, the image is stored as a matrix where each element is used to store color information to store color information for each pixel. This study uses the Ratcliff/Obershelp algorithm and Levenshtein Distance is an image search algorithm that is carried out by searching for matches of the same rgb value in the image. The Ratcliff/Obershelp and Levenshtein Distance algorithms are carried out in detail by displaying the query value of the image similarity level and the part that it executes and displaying images in PNG, BMP, JPEG, ICO and JPG against image similarity search.